MEGA EVENT SAIL BANDA 2010 PERANGKAT PEMBANGUNAN KEMBALI KOTA AMBON PASCA KONFLIK - , Henry L. J. Tanasale ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mega event is the largest-scale event with an international reputation. Mega event were able to entangled a huge number of attendees, as well as providing significant benefits for hosting in optimization of the various typologies of urban redevelopment. Surely, this re-development will give long-term and multi-sectoral impact (Masterman, 2009). Ambon is one of a fairly intense city that use event as the urban redevelopment instrument. After conflict in Moluccas on 19th of January 1999, which led to the destruction of infrastructure in Ambon city, the government try to find an instant solution to accelerate the development process, include using national and international events like mega event of Sail Banda 2010 (held on July 27 to August 8, 2010). Visibly, the role of international yacht race has a great significance in post-conflict redevelopment in Ambon city, as well as a development catalyst or stimulant in various sectors (Sahusilawane, 2012). Based on the reasons which explained earlier, a general question appointed is how was the relevance process, impact and continuity, also the factors that influence the successful of mega event Sail Banda 2010, as an instrument for postconflicts redevelopment in Ambon city? For that reason, consideration of this study titled: âMega Event of Sail Banda 2010: An Instrument for Post-conflicts Redevelopment in Ambon City.â In order to find a good explanation of that question, this research uses the explanatory case study method with various preposition as substance of verification in field. This study has found a kind of positive impact which derive from Sail Banda for a framework of continuity development in Ambon City. In addition, this event was appreciable to catalyzed the physical redevelopment of Ambon, and also enable to build and imiging spirit of reconciliation and safety among society after conflict. Moreover, in several years, Sail Banda deliver a great significance to stimulate the growth accelerating of important sectors in Ambon city. With that kind of significance, Sail Banda was appreciabled as one of the unique event which successfully re-development Ambon city post conflict.